A Bibliometric Analysis of Pragmatics and Speech Act Research (2015–2025): A Scopus-Based Study - Zulfikri Zulfikri (Datokarama English Education Journal, 2026)
This study mapped the global landscape of pragmatics and speech act research through a bibliometric approach. A corpus of 1,346 Scopus-indexed articles and reviews published between 2015 and 2025 was analyzed using the bibliometrix package in R and Biblioshiny, examining publication trends, citation patterns, and network structures including co-authorship, co-citation, and keyword co-occurrence. The findings revealed a sustained growth in research output (annual growth rate: 10.1%), sustained by a small set of core journals, most prominently the Journal of Pragmatics, and a group of highly prolific authors distributed across institutions in Europe, East Asia, and the Middle East. Theoretically, the field remained anchored in foundational constructs derived from speech act theory, politeness, and interlanguage pragmatics, while emerging areas such as digital discourse, corpus-based approaches, and computational applications had gained increasing visibility. Co-citation analysis identified Austin (1962), Searle (1979), and Brown and Levinson (1987) as the most consistently cited intellectual anchors. The co-word network revealed a conceptual structure centered on speech acts and pragmatics, with interconnected clusters related to politeness and interactional norms, specific speech-act types such as requests and apologies, and emerging computational or data-driven approaches. Taken together, the results sketched a field that had grown substantially over the decade, consolidated around a recognizable set of theoretical anchors, and opened up toward new methods, media, and cross-linguistic contexts.